Gender disparities in agricultural extension among smallholders in Western Uganda - Midamba, Dick Chune; Ouko, Kevin Okoth (Taylor & Francis, 2024)
In this study, we aimed to assess gender disparities in access to agricultural extension services and the determinants of access to extension among male and female-headed households in Western Uganda. A cross-sectional survey was conducted to extract primary data from 200 farmers using a semi-structured questionnaire. The collected data were analyzed using descriptive statistics and Binary Logit model. Our findings revealed that majority of the male-headed households had access to extension compared to their female-headed household counterparts. This was also evident in the sources of agricultural extension. The socio-demographic characteristics of farmers also indicated that male-headed households were better off in many areas, for example, male-headed households boasted 498.83 kg/ha maize productivity, while households headed by females produced 405.36 kg/ha, indicating a 94 kg/ha yield gap. Similarly, adoption of agricultural practices was high among the male-headed households than their fellow female-headed counterparts. Finally, the estimates from the Binary Logit revealed that male-headed households’ access to extension was influenced by age, education, farm size, crop diversity, and group membership. The predictor variables that significantly influenced female-headed households’ access to extension include age, education, experience, household size, farm size, distance to extension, crop diversity, non-farm income, and credit access. The study concluded that there are gender disparities in agricultural extension as evident in the access to, sources and determinants of access to agricultural extension. To bridge the gender gap, the study advocates for more training and extension services to female-headed households regarding access to and sources of extension services.
Keywords: Gender disparity; Extension; Productivity; Western Uganda; Gender analysis